2022
DOI: 10.1007/s11739-022-02997-9
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-4 (FIB-4) Index and mortality in COVID-19 patients admitted to the emergency department

Abstract: Liver damage worsens the prognosis of coronavirus 19 disease (COVID-19). However, the best strategy to stratify mortality risk according to liver damage has not been established. The aim of this study is to test the predictive value of the validated Fibrosis-4 (FIB-4) Index and compared it to liver transaminases and to the AST-to-Platelet ratio index (APRI). Multicenter cohort study including 992 consecutive COVID-19 patients admitted to the Emergency Department. FIB-4 > 3.25 and APRI > 0.7 were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Furthermore, our work confirms that ferritin levels and liver damage (in the form of hepatic steatosis) worsens the prognosis of COVID-19, as already shown by Bucci and colleagues [ 55 ] and by our group [ 3 , 4 ]. A further step was to develop a model that could predict the risk of lung impairment and the need for oxygen therapy in COVID-19 patients by integrating clinical characteristics and laboratory parameters for each patient.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our work confirms that ferritin levels and liver damage (in the form of hepatic steatosis) worsens the prognosis of COVID-19, as already shown by Bucci and colleagues [ 55 ] and by our group [ 3 , 4 ]. A further step was to develop a model that could predict the risk of lung impairment and the need for oxygen therapy in COVID-19 patients by integrating clinical characteristics and laboratory parameters for each patient.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our confirms that ferritin levels and liver damage (in the form of hepatic steatosis) worsens the prognosis of COVID-19, as already shown by Bucci and colleagues [54] and by our group [3,4]. A further step was to develop a model that could predict the risk of lung impairment and the need for oxygen therapy in COVID-19 patients by integrating clinical characteristics and laboratory parameters for each patient.…”
Section: Discussionsupporting
confidence: 82%
“…Second, age is a very important factor, because it is in the numerator of the FIB-4 formula and the authors reported a statistically significant difference (p < 0.001) in the age in the group of patients with a FIB-4 > 3.25 for the group with a FIB-4 < 3.25 with a mean age of 76 (70-81) and 57 (51-64), respectively [1].…”
Section: Dear Editormentioning
confidence: 99%
“…We read with great interest the article by Bucci et al, which investigated the Fibrosis-4 (FIB-4) Index and mortality in COVID-19 patients admitted to the emergency department [1].…”
Section: Dear Editormentioning
confidence: 99%